2020
DOI: 10.1016/j.redox.2020.101670
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inhibits ferritinophagy, increases mitochondrial ferritin, and protects from ferroptosis

Abstract: Cellular iron, at the physiological level, is essential to maintain several metabolic pathways, while an excess of free iron may cause oxidative damage and/or provoke cell death. Consequently, iron homeostasis has to be tightly controlled. Under hypoxia these regulatory mechanisms for human macrophages are not well understood. Hypoxic primary human macrophages reduced intracellular free iron and increased ferritin expression, including mitochondrial ferritin (FTMT), to store iron. In parallel, nuclear receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(171 citation statements)
references
References 43 publications
7
149
0
Order By: Relevance
“…However, our experiment with iron co-treatment demonstrated that iron potentiates the effect of RSL3. Recently it was shown that knockdown of FTH and mitochondrial ferritin sensitized human macrophages and fibrosarcoma cells for RSL3-induced ferroptosis, demonstrating that ferritin protects cells also from ferroptotic cell death induced by GPX4 inhibition [53]. Even if it is partially in disagreement with our results where cells with higher ferritin level (NCOA4 KO cell line) are more sensitive for RSL3-induced ferroptosis, it may suggest that the observed effect in our cell clones may be due to the other mechanism unrelated to ferritin level.…”
Section: Discussionmentioning
confidence: 99%
“…However, our experiment with iron co-treatment demonstrated that iron potentiates the effect of RSL3. Recently it was shown that knockdown of FTH and mitochondrial ferritin sensitized human macrophages and fibrosarcoma cells for RSL3-induced ferroptosis, demonstrating that ferritin protects cells also from ferroptotic cell death induced by GPX4 inhibition [53]. Even if it is partially in disagreement with our results where cells with higher ferritin level (NCOA4 KO cell line) are more sensitive for RSL3-induced ferroptosis, it may suggest that the observed effect in our cell clones may be due to the other mechanism unrelated to ferritin level.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways have been implicated in the activation of NCOA4 expression, ferritinophagy, and ferroptosis. JNK pathway has been implicated in hypoxia‐regulated NCOA4 transcription by targeting microRNA 6862‐5p, and phosphoinositide 3‐kinase is also involved in the transcription of NCOA4 in a hypoxic condition, 38 while c‐JUN N‐terminal kinase and p38 activation were involved in cell death of erastin‐treated HL‐60 cells 39 . Cold stress triggers ferroptosis by the ASK1‐p38 MAPK pathway, 40 while our present study indicated that phosphorylation of p38 MAPK promoted NCOA4 expression in P .…”
Section: Discussionmentioning
confidence: 99%
“…miR-6862 is a relatively novel miRNA with its functions largely unknown. Fuhrmannet al, demonstrated that miR-6862 silenced nuclear receptor coactivator 4 (NCOA4) to inhibit mitochondrial ferritin (FTMT) formation [ 37 ]. Zhu et al, reported that miR-6862 expression is dysregulated in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%